Desarrollo de un modelo de optimización para el despacho hidrotérmico a corto plazo con multiembalse. - Ortiz Malla, Josue Steeven (2021)
Short-term hydrothermal coordination is defined as one of the most important and challenging scheduling problems, whose objective is to satisfy the hourly demand considering the minimum cost of electricity production. In this project, a scheduling model for short-term hydrothermal operation, developed for daily operation using the GAMS environment, is proposed. The hydrothermal coordination problem is solved using an equivalent cost function for the thermal units, while the economic dispatch is solved using the hydrothermal coordination constraints, to minimize the generation costs, take into account the quadratic cost functions of thermal units, and the second-degree equation relating the reservoir characteristics to calculate the generated power of hydroelectric power plants. Therefore, a nonlinear programming (NLP) optimization algorithm using algebraic modeling is employed to solve nonlinear power system operation problems. The proposed method is employed on four test systems to evaluate the performance of the optimization method applied in the short-term hydrothermal coordination problem.